The Koryak. Memoirs of the AMNH - Jochelson, Waldemar, 1855-1937. (Leiden, E. J. Brill ltd.; New York, G. E. Stechert, 1905)
2 v. illus., XL pl., fold. map. 36 cm. "Authorities quoted": p. 3-11. pt. 1. Religion and myths of the Koryak.-- pt. 2. Material culture and social organization of the Koryak. Cover of PDF belongs with whole series.